2015
DOI: 10.1108/caer-11-2013-0153
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of consumer demand for traceable pork in China based on a real choice experiment

Abstract: Purpose – The purpose of this paper is to reveal the actual consumer demand for traceable pork by investigating consumer preferences for pork with combined levels of traceability information based on differences in individual consumer preferences, in order to support the government in decision making regarding the gradual construction of safe food markets. Design/methodology/approach – Combinations of four types of traceability informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…Olesen, Alfnes, Røra, and Kolstad () used a similar method and demonstrated that consumers were willing to pay a premium for organic and animal welfare‐labeled salmon. A few others followed similar view of research (Alfnes, Guttormsen, Steine, & Kolstad, ; Q. Chen, Anders, & An, ; Ginon, Chabanet, Combris, & Issanchou, ; Gracia, ; Moser, Raffaelli, & Notaro, ; Volinsky, Adamowicz, Veeman, & Srivastava, ; Wu, Wang, & Zhu, ).…”
Section: Background and Literature Reviewmentioning
confidence: 81%
See 1 more Smart Citation
“…Olesen, Alfnes, Røra, and Kolstad () used a similar method and demonstrated that consumers were willing to pay a premium for organic and animal welfare‐labeled salmon. A few others followed similar view of research (Alfnes, Guttormsen, Steine, & Kolstad, ; Q. Chen, Anders, & An, ; Ginon, Chabanet, Combris, & Issanchou, ; Gracia, ; Moser, Raffaelli, & Notaro, ; Volinsky, Adamowicz, Veeman, & Srivastava, ; Wu, Wang, & Zhu, ).…”
Section: Background and Literature Reviewmentioning
confidence: 81%
“…The design of our experiments followed that of Wu et al, () with some minor modifications. Before the experiment, 15 boxes, corresponding to the 15 choice sets in the questionnaire, were placed on a table.…”
Section: Methodological Backgroundmentioning
confidence: 99%
“…Through a reliable and continuous security information flow on the supply chain, food traceability information could ensure the traceability of food, in order to monitor food production process and flow direction to identify the source of problems and recall through traceability (Regattieri, 2007). Wu, Wang, and Zhu (2015a) investigated Chinese consumer WTP for traceability information, and their results indicated that quality certification was the most important characteristic, followed by appearance and traceability information. Ortega, Wang, Wu, and Olynk (2011) reported that Chinese consumers were willing to pay premium for government-certified traceable food.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, the traceability information included in the IMF traceability system must be scientifically defined based on the actual IMF safety risks in China (Wu et al, 2015a). Therefore, the traceability information included in the IMF traceability system must be scientifically defined based on the actual IMF safety risks in China (Wu et al, 2015a).…”
Section: Attribute and Level Settingsmentioning
confidence: 99%
See 1 more Smart Citation